New Insights of Phospholipase A2 Associated Neurodegeneration Phenotype Based on the Long-Term Follow-Up of a Large Hungarian Family - Toth-Bencsik, Renata; Balicza, Peter; Varga, Edina Timea; Lengyel, Andras; Rudas, Gabor; Gal, Aniko; Molnar, Maria Judit (Frontiers in Genetics, 2021)
Introduction Phospholipase A2-associated Neurodegeneration (PLAN) is a group of neurodegenerative diseases associated with the alterations of PLA2G6. Some phenotype-genotype association are well known but there is no clear explanation why some cases can be classified into distinct subgroups, while others follow a continuous clinical spectrum. Methods Long-term neurological, and psychiatric follow-up, neuropathological, radiological, and genetic examinations, were performed in three affected girls and their family. Results Two 24-years old twins and their 22-years old sister harbored the p.P622S, and p.R600W mutation in PLA2G6. The age of onset and the most prominent presenting symptoms (gaze palsy, ataxia, dystonia, psychomotor regression indicated atypical neuroaxonal dystrophy (ANAD), however, optic atrophy, severe tetraparesis would fit into infantile neuroaxonal dystrophy (INAD). All siblings had hyperintensity in the globi pallidi and substantiae nigrae which is reported in ANAD, whereas it is considered a later neuroradiological marker in INAD. The slow progression, rigidity, bradykinesis, and the prominent psychiatric symptoms indicate PLA2G6-related dystonia-parkinsonism. Abnormal mitochondria, lipid accumulation and axonal spheroids were observed in the muscle and nerve tissue. Brain deposition appeared 6 years following the initial cerebellar atrophy. Mild MRI alterations were detected in the asymptomatic carrier parents. Conclusion The colorful clinical symptoms, the slightly discordant phenotype, and the neuroimaging data in the family supports the view that despite the distinct definition of age-related phenotypes in PLAN, these are not strict disease categories, but rather a continuous phenotypic spectrum. The mild MRI alterations of the parents and the family history suggest that even heterozygous pathogenic variants might be associated with clinical symptoms, although systematic study is needed to prove this.